2012
DOI: 10.1590/s0101-28002012000100013
|View full text |Cite
|
Sign up to set email alerts
|

Uso a longo prazo de enalapril e hidroclorotiazida em dois pacientes com novas mutações com doença de Dent tipo 1

Abstract: Dent's disease type 1 is an X-linked tubular disease caused by mutations in the renal chloride channel CLCN-5, and it is characterized by low molecular weight proteinuria, hypercalciuria, nephrocalcinosis, and renal failure. Several cases have been described in which the only presenting symptoms were asymptomatic proteinuria, and focal segmental or global glomerulosclerosis. The renal failure in these patients may be caused by hypercalciuria and persistent proteinuria. Therefore, angiotensin converse enzyme in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…A high potassium citrate diet has been shown to reduce urinary calcium and delay renal failure in animal experiments (16). There is no clear evidence that ACEI drugs reduce urinary protein in patients with Dent disease (17).…”
Section: Discussionmentioning
confidence: 99%
“…A high potassium citrate diet has been shown to reduce urinary calcium and delay renal failure in animal experiments (16). There is no clear evidence that ACEI drugs reduce urinary protein in patients with Dent disease (17).…”
Section: Discussionmentioning
confidence: 99%
“…A similar promising reduction in urine total protein was observed in two boys with less than 1 year of treatment, and the histologic findings were FSGS and extensive mesangial deposition of C1q (Copelovitch, Nash, & Kaplan, 2007; Lim, Yun, Moon, & Cheong, 2007). However, it has also been reported that the level of urine total protein in some patients failed to respond to ACE inhibitor and/or ARB therapy after a maximum of 5 years (Blanchard et al., 2016; Cramer et al., 2014; Frishberg et al., 2009; Vaisbich et al., 2012); unfortunately, data on the efficacy of these drugs on albuminuria were not available. Our results showed that, in half of the children, albuminuria could be controlled with ACE inhibitor and/or ARB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A keresés eredményeként összesen 63 közleményt találtunk, melyekből 59-et tudtunk áttekinteni. A közlemények közül azt a 19 tanulmányt elemeztük, amelyben a genetikai diagnózis mellett a betegek vese biopsziás vizsgálatának a lelete is közlésre került [3,6,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. A hisztopatológiai leírások vizsgálatán túl a klasszikus Dent-betegséghez tartozó klinikai eltéréseket is elemeztük.…”
Section: Genetikai Háttérunclassified